Isolation of Mycorrhizal Fungi from Maize Cultivation Soil and the Production of Biofertilizer from These Fungi - Thi Hoang Yen, Le; Anh, Le Hong; Linh, Mai Thi Dam; Hop, Duong Van (VNU Journal of Science: Natural Sciences and Technology, 2018)
A total of 3,179 Arbuscular Mycorrhizal Fungus (AMF) spores were isolated from 30 maize cultivation soil samples collected in Hanoi and Ha Nam. The spores were analyzed under a microscope at 200× magnification and grouped into 8 genera with 27 species of AMF according to their morphological characteristics including shape, size, colour and wall structures. Three out of the identified genera with 9 species were regarded as novel taxa and the species of Dentiscutata , Racocetra, Rhizophagus and Septoglomus were, for the first time, reported about in Vietnam. Acaulospora, Gigaspora and Glomus were the dominant genera with the occurence frequency ranging from 13.4% to 40.2%. A. Longula , G. Decipien , G. Gingatea and Glomusmulticaule were evaluated for their ability to propagate in the maize host. Media containing silica sand, coconut bark and rich soil in different ratios were used for propagating AMF. After 5 weeks’ innoculation, Acaulospora showed the best propagation in the medium with silica sand, coconut bark and rich soil mixed in the ratio of 1:1:1, followed by Gingaspora and Glomus . The number of spores propagated from Gingaspora and Acaulospora ranged from 250 to 331 spores/ 100g substrates. The study also shows that AMF could propagate in the host at the IP of 1217.8 and could enhance the innoculated maize’s body weight, height and ear by 40.0%, 58.9% and 24.9%, respectively. Keywords Arbuscular mycorrhizal fungus, diversity, bio-fertilizer, maize root, taxonomy References [1] Bever JD, Morton JB, Antonovics J, Schultz PA(1996) Host-dependent sporulation and species diversity of Arbuscular Mycorrhiza fungi in a mown grassland, J Ecol 84: 63-71. [2] Lee J, Lee S & Young JPW (2008) Improved PCR primers for the detection and identication of Arbuscular Mycorrhizalfungi. FEMS Microbiol Ecol 65:339–349. [3] Morton JB(1988) Taxonomy of VA mycorrhizal fungi: classification, nomenclature, and identification. Mycotaxon 37: 259-267. [4] Gerdemann JW and TH Nicolson TH(1963) Spores of mycorrhizal Endogone species extracted from soil by wet-sieving and decanting, Trans. Br. Mycol. Soc. 46: 228-235. [5] Choi YW, Hyde KD and Ho WH (1999) Single spore isolation of fungi, Fungal Diversity, 3:1- 29. [6] Liu RJ and Lua XS (1994) “A new method to quantify the inoculum potential of arbuscular mycorrhizal fungi”. New Phytol, 128, 89-92. [7] Morton JB and Benny GL(1990) Revised classification of Arbuscular Mycorrhizal fungi, a new order Glomales, two new sub-orders Glomineae and Gigasporinae and two new families Acaulosporaceae and Gigasporaceae with an emendation of Glomaceae, Mycotaxon 37: 462- 471. [8] http://invam.caf.wvu.edu. [9] Zhao ZW, Wang GH and Yang L(2003) Biodiversity of Arbuscular Mycorrhizal fungi in tropical rain forests of Xishuangbanna, southwest China, Fungal Diversity 13: 225-233. [10] Brown (2015) Workshop on Biofertilizer. IMBT- VNU [11] Đỗ Thị Xuân (2016) Khảo sát sự xâm nhiễm và sự hiện diện các bào tử nấm rễ nội cộng sinh (AM) trong đất vùng rễ và rễ của cây bắp, mè và ớt được trồng ở Thành phố Cần Thơ. Tạp chí Đại học Cần Thơ, 46B: 47-53. [12] Trần thị Dạ Thảo (2012) Nghiên cứu sự cộng sinh của nấm Mycorrhiza trên cây ngô (Zae Mays L) vùng Đông Nam Bộ. Luận án TS Đại học Nông Lâm TPHCM. [13] Võ Thị Tú Trinh và Trương Minh (2017) Sự phân bố và xâm nhiễm của nấm rễ nội cộng sinh Arbuscular Mycorrhizae (VAM) trong mẫu rễ và đất trồng bắp tại một số tỉnh đồng bằng sông Cửu Long. Tạp chí Khoa học trường Đại học Cần Thơ. Phần B: Nông nghiệp, thủy sản và Công nghệ Sinh học, 53:105-111. [14] Trần Thị Như Hằng, Trần Thị Hồng Hà, Nguyễn Đình Luyện, Posta Katalin, Lê Mai Hương (2012) Phân lập, nhân nuôi lưu giữ và định tên một số nấm rễ nội cộng sinh trên cây lúa và cà chua ở Bắc Việt Nam, Tạp chí Khoa học và Công nghệ 50 (4) 521. [15] Wang YY, Vestberg M, Walker C, Hurme T, Zhang XP, Lindström K(2008), Diversity and infectivity of Arbuscular Mycorrhizal fungi in agricultural soils of the Sichuan Province of mainland China, Mycorrhiza:1868. [16] Guadarrama P and Alvarez-Sanchez FJ(1999)Abundance of Arbuscular Mycorrhizal fungi spores in different environments in a tropical rain forest, Veracruz, Mexico, Mycorrhiza, 258-267. [17] Hajilou M, Abbasdokht M, Amerian M and Gholami A (2010) Function of biologic fertilizers on growth characteristics, yield and yield components of maize in agriculture ecosystem. The first national congress of sustainability agriculture and healthy crop productio